SIMPLES Nnaciona: repercussão na arrecadação do ICMS nas empresas cearenses - Romero, Tarso Espíndola (2009)
Given the importance of micro and small enterprises for the economy and the Brazilian society, the government issued a supplementary law 123/2009, known as Single National (SN). One of his goals is to relieve companies of State, Federal and Local government taxes, unifying the collection of eight charges in only one document collection, the other goal is to include businesses in the formal sector, since the law has facilitated the registration process of companies more agile and without bureaucracy. Analyzing the main state tax (ICMS), our research has centered on discussion of the effect of implementing the National Single on the amount of business in Ceará, in relation to tax collection, and noted that the statewide impact of this new rule brought in regard to starting a business in the state of Ceará. The result suggests that after the implementation of SN the number of registered companies has increased considerably compared to the number of companies registered before the implementation of SN. Moreover, the impact of the implementation of SN in the collection of the companies investigated is neutral, statistically, except only for those in the food sector, where the deployment of SN led to the increase in the collection of ICMS.